FAKTOR PENDORONG IRAN MENYETUJUI KESEPAKATAN NUKLIR JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) TAHUN 2013 – 2017 - Mahayanti, Ni Putu Denik; Fasisaka, Idin; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT   Iran's nuclear development has changed the instability of Iran’s economy. Iran’s economic sanction initiated resistance economy as an action of Iran’s governments defense. The pressure of economic sanctionscontinue to increase with the development of Iran’s nuclear that makes Iran’s governments couldn’t handle the stability of Iran’s economy. Based on that situation, Iran’s governments response was took an attempt for negotiation as a choice to overcome the tensions post Iran’s economic sanctions. As the end of that negotiation created Joint Comprehensive Plan of Action (JCPOA) nuclear agreement. That agreement made by Iran and P5 + 1 group (United Kingdom, France, China, Russian Federation, The United States + Germany) at July 14, 2015. This research aims to analyse factors behind Iran’s approve the JCPOA nuclear agreement. The locus of this study is from 2013 to 2017.   Keywords: Nuclear Development, Resistance Economy, negotiation, JCPOA, P5 +1